PENGARUH PEMANGKASAN CABANG DAN BEBERAPA JENIS VARIETAS TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH (CAPSICUM ANNUM L) DI DESA NANOWA - Adirlina Laia (Jurnal Sapta Agrica, 2025)
This study aimed to determine the effect of branch pruning and several varieties on the growth of red chili plants. The research was conducted at the Agrotechnology practicum field. A randomized block design (RBD) with two factors was used: the first factor consisted of two varieties, V1 (TM999) and V2 (Lado F1), while the second factor included three levels, namely P0 (no treatment), P1 (field-top pruning), and P2 (side-shoot pruning). Each treatment consisted of five plants. The observed data were analyzed using analysis of variance (ANOVA) and followed by an LSD test at a 5% significance level. The results showed that branch pruning significantly affected the vegetative growth of red chili plants in almost all observed parameters. Plant height exhibited a consistent response at all observation periods (1–4 WAP), the number of leaves showed a significant response after the initial adaptation phase (3–4 WAP), and stem diameter increased significantly at 4 WAP.